Cultivating Microalgae with Biophotovoltaic to Produce Bioelectricity: A Bibliometric Analysis - Nur, Muhamad Maulana Azimatun; Desta K. H, Raden Herjun; Pratama, Ryan Keane Mahardika; Affrida, Amanda Nur; Putri, Aulia Rahma; Puspitaningrum, Dwi Aulia; Hasanuzzaman, Md.; Dewi, Resti Nurmala (Institut Teknologi Sepuluh Nopember, 2024)
This review investigates the role of microalgae in bioelectricity production through biophotovoltaic (BPV) systems, focusing on their dual benefits of generating renewable energy and treating wastewater while capturing CO2. The objective of this paper is to conduct a bibliometric analysis of publications from 2013 to 2024 to understand research trends, key contributors, and research hotspots in the field of microalgae-based BPV systems. Methods used include statistical analysis through VOSviewer to visualize the connections between articles and authors. The results show significant advancements in integrating of nanomaterials and microbial fuel cell technologies for bioelectricity generation, as well as ongoing challenges in scalability, voltage balance, and material optimization. This review provides insights into future research directions for improving BPV systems.